Feeding/Eating Problems in Children Who Refrained From Treatment in the Past: Who Did (Not) Recover? - Dumont, Eric; Jansen, Anita; Duker, Pieter C.; Seys, Daniel M.; Broers, Nick J.; Mulkens, Sandra (Frontiers in Pediatrics, 2022)
Background Young children with disordered feeding may be at increased risk for problematic eating in the future. This retrospective study attempts to identify predictors of later feeding problems. Objectives Children (N = 236) with disordered feeding, who refrained from behavioral treatment after consultation at a tertiary treatment center for feeding and eating problems were followed-up after, on average, 6 years and 3 months (timepoint 2). Method Logistic regressions were carried out with characteristics taken at intake (timepoint 1)—sex, pre/dysmaturity, gastro-intestinal disease, history of age-adequate feeding, syndrome/developmental impairment, autism spectrum disorder, comorbidity, age, and several variables of a restrictive- and selective food intake—and duration between timepoint 1 and 2, as predictor variables, and age-appropriate food intake at t2 as the dependent variable. Results Despite improvement over time, 63% did not reach an age-adequate food intake at t2. Predictors of age-inadequate food intake were: (a) older age; (b) sex (male), (c) longer duration between timepoint 1 and timepoint 2; (d) autism spectrum disorder; (e) selective texture choices and (f) lack of varied nutritional intake. Conclusion This study shows that most untreated young children's feeding problems do not improve over years. Besides the advice to seek help at an early age, it seems especially recommended to treat (male) children with autism spectrum disorder and selective feeding patterns.